Relational Aspects of Computer-Mediated Communication: Experimental Observations over Time - Walther, Joseph B. (Organization Science, 1995)
Previous research on the interpersonal effects of computer-mediated communication (CMC) reveals inconsistencies. In some cases CMC has been found to be impersonal, task-oriented, and hostile. Other reports show warm personal relations, and still others show gradual adjustments in interpersonal relations over time. The past research results are also difficult to compare, as their research methods reveal inconsistent approaches. These inconsistencies include the treatment of time limits on group development, the neglect of nonverbal behavior in face-to-face, comparison groups, and other measurement issues. Each of these factors may obscure our understanding of the way CMC partners get to know and come to relate to each other through CMC. The present study attempts to address some of these concerns. This study explored the effects of computer conferencing on the interpersonal messages with which people define their relationships, known as relational communication. Observers rated the relational communication from transcripts of CMC conversations or from videotapes of face-to-face three-person groups who had worked in several sessions. Analyses showed that CMC groups achieved more positive levels on several dimensions of interpersonal communication than did face-to-face groups. On other dimensions, no differences between conditions were found. In no case did CMC groups express less intimacy or more task-orientation than face-to-face groups. Implications are drawn suggesting that under certain conditions, CMC may promote positive relational effects in ways that previous theories have not considered, and in some ways superior to more traditional media.